The exploration of remote simulation strategies for the acquisition of psychomotor skills in medicine: a pilot randomized controlled trial - Natasha Guérard-Poirier; Léamarie Meloche-Dumas; Michèle Beniey; Andrei Torres; Bill Kapralos; Malek Dhane; Frédéric Mercier; Rami Younan; Adam Dubrowski; Erica Patocskai (Springer, 2023)
Abstract Background Progress in remote educational strategies was fueled by the advent of the COVID-19 pandemic. This pilot RCT explored the efficacy of a decentralized model of simulation based on principles of observational and peer-to-peer learning for the acquisition of surgical skills. Methods Sixty medical students from the University of Montreal learned the running subcuticular suture in four different conditions: (1) Control group (2) Self-learning (3) Peer-learning (4) Peer-learning with expert feedback. The control group learned with error-free videos, while the others, through videos illustrating strategic sub-optimal performances to be identified and discussed by students. Performance on a simulator at the end of the learning period, was assessed by an expert using a global rating scale (GRS) and checklist (CL). Results Students engaging in peer-to-peer learning strategies outperformed students who learned alone. The presence of an expert, and passive vs active observational learning strategies did not impact performance. Conclusion This study supports the efficacy of a remote learning strategy and demonstrates how collaborative discourse optimizes the students' acquisition of surgical skills. These remote simulation strategies create the potential for implantation in future medical curriculum design. Trial Registration: NCT04425499 2020-05-06.